Individual and collective memory consolidation : analogous processes on different levels - Anastasio, Thomas J. (MIT Press, 2012)
An argument that individuals and collectives form memories by analogous processes and a case study of collective retrograde amnesia. We form individual memories by a process known as consolidation: the conversion of immediate and fleeting bits of information into a stable and accessible representation of facts and events. These memories provide a version of the past that helps us navigate the present and is critical to individual identity. In this book, Thomas Anastasio, Kristen Ann Ehrenberger, Patrick Watson, and Wenyi Zhang propose that social groups form collective memories by analogous processes. Using facts and insights from neuroscience, psychology, anthropology, and history, they describe a single process of consolidation with analogous--not merely comparable--manifestations on any level, whether brain, family, or society. They propose a three-in-one model of memory consolidation, composed of a buffer, a relator, and a generalizer, all within the consolidating entity, that can explain memory consolidation phenomena on individual and collective levels. When consolidation is disrupted by traumatic injury to a brain structure known as the hippocampus, memories in the process of being consolidated are lost. In individuals, this is known as retrograde amnesia. The authors hypothesize a "social hippocampus" and argue that disruption at the collective level can result in collective retrograde amnesia. They offer the Chinese Cultural Revolution (1966-1976) as an example of trauma to the social hippocampus and present evidence for the loss of recent collective memory in mainland Chinese populations that experienced the Cultural Revolution